2018
DOI: 10.1186/s12960-018-0316-6
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of health professional education across five Asian countries—a protocol

Abstract: BackgroundThere is an increasing consensus globally that the education of health professionals is failing to keep pace with scientific, social, and economic changes transforming the healthcare environment. This catalyzed a movement in reforming education of health professionals across Bangladesh, China, India, Thailand, and Vietnam who jointly volunteered to implement and conduct cooperative, comparative, and suitable health professional education assessments with respect to the nation’s socio-economic and cul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
2

Relationship

4
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…Public health curricula must be designed with a focus on meeting current demand, capturing broad determinants of health and providing sufficient guidance for career pathways and active public health practice post their completion [ 10 ]. We found that a range of training opportunities do exist, but that the direct linkage with career opportunities is not consistent or sufficient yet.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Public health curricula must be designed with a focus on meeting current demand, capturing broad determinants of health and providing sufficient guidance for career pathways and active public health practice post their completion [ 10 ]. We found that a range of training opportunities do exist, but that the direct linkage with career opportunities is not consistent or sufficient yet.…”
Section: Discussionmentioning
confidence: 99%
“…However, previous work has identified that MPH curriculums were not standardized, nor overseen by an accrediting institution at the national or international level [ 14 , 16 18 ]. There remain high concentrations of professionals from medical backgrounds in public health training programs, which though important, leave many other potential entry points to public health such as social work, nutrition, nursing, and education among others underrepresented [ 1 , 10 , 17 ]. This relates to another necessary and valuable component of a strong public health workforce—a transdisciplinary, multisectoral approach—which is essential to addressing the broader social and environmental determinants of health; thus far, this potential has not been able to be fully leveraged [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several interviewees expressed interest in improving collaborations. The complexities of health professional education bene t from networks between and within training institutions, government ministries, health sector employers, and other stakeholders (14). That said, partnerships can be challenging to manage, and there can be di culties associated with how to effectively share expertise or navigate competing priorities or power dynamics.…”
Section: Discussionmentioning
confidence: 99%
“…Public health and maternal child health (MCH) courses must be designed with a focus on meeting current demand, capturing broad determinants of health and providing su cient guidance for career pathways and active public health practice post their completion (2). We found that a range of training opportunities do exist, but that the direct linkage with career opportunities is not consistent or su cient yet.…”
mentioning
confidence: 99%